2011
DOI: 10.1007/s00148-011-0385-5
|View full text |Cite
|
Sign up to set email alerts
|

Do fundraisers select charitable donors based on gender and race? Evidence from survey data

Abstract: Recent studies document that people are much more likely to donate to charity and volunteer their time when they are asked to. Using household surveys of giving and volunteering in the United States conducted from 1992 to 2001, which contain questions on whether the respondent was personally asked to give or volunteer, this paper investigates the factors associated with the probability of receiving a charitable solicitation and presents substantial evidence that race and gender di¤erences play key roles in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Yoruk examined race and gender differences in the probability of being asked to donate to a cause [14]. Using nonlinear decomposition techniques with data on U.S. giving collected between 1992 and 2001, the study found that blacks are 12% less likely than whites to be asked to give, while nonwhite Hispanics were 26% less likely to be asked to give.…”
Section: Past Researchmentioning
confidence: 99%
“…Yoruk examined race and gender differences in the probability of being asked to donate to a cause [14]. Using nonlinear decomposition techniques with data on U.S. giving collected between 1992 and 2001, the study found that blacks are 12% less likely than whites to be asked to give, while nonwhite Hispanics were 26% less likely to be asked to give.…”
Section: Past Researchmentioning
confidence: 99%
“…Fundraisers in general are predominately White (Bureau of Labor Statistics, ). Although this is beyond the scope of our current study, we encourage future investigators to remain attentive to the complex ways in which race may be related to career choice, career opportunities, professional development activities, and personal philanthropic activities (see, e.g., Jones, ; Yörük, ). Gender, too, may play a complex role in the fundraiser's journey, and future researchers should be attune to the gender‐related motivations to become (or not become) a fundraiser.…”
Section: Discussion: Moving Toward a Research Agendamentioning
confidence: 98%
“…In addition, research conducted by Yörük (2012) found that White individuals are solicited to volunteer more often than people of other races, and women are solicited to volunteer more often than are men. Indeed, recent survey findings indicated that most fundraisers are White women (Breeze & Dale, 2020; Dale, 2017).…”
Section: General Research On Solicitationmentioning
confidence: 99%